$K$-contact generalized square Finsler manifolds - Hannaneh Faraji; Behzad Najafi Saghezchi; Tayebeh Tabatabaeifar (AUT Journal of Mathematics and Computing)
We study almost contact generalized square Finsler manifolds and introduce the notion of $K$-contact Finsler structures. Then, we characterize generalized square $K$-contact almost contact manifolds. As an application, we show that every $3$-dimensional Lie group admits a left-invariant generalized square Finsler structure.